Perception of COVID-19 infection risk among students in healthcare professions: a qualitative study - Bandini, Stefania; Valentini, Orietta; Dal Fiume, Cinzia; Deserri, Deborah; Gaddoni, Claudio; Martinelli, Stefano; Montalti, Matteo; Negretti, Francesca Maria; Olmi, Sabina; Rossi, Elena; Sacchetti, Cleta; Vannini, Valeria (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work: The aim of this study was to describe how students in healthcare professions perceived the risk of COVID-19 infection during their curricular internships in the post-lockdown period, in order to evaluate possible corrective and/or improvement actions to ensure future safe learning experiences.Methods: Is a descriptive qualitative study conducted in March 2021 using Focus Groups, with the participation of students from all the involved study programs, based on a voluntary proactive sampling approach. The study was conducted among students in healthcare professions at the University of Bologna, in collaboration with the Local Health Authority of Imola, who were undertaking curricular internships in various public or private healthcare, social, and non-healthcare settings, as specified in the educational plan.Results: The results showed that the students reported having knowledge about preventive measures to avoid infection, being attentive observers of the organizational aspects within their internship contexts, and considering the internship tutor as a significant guiding figure in their perception of risk and the related measures to be adopted. Despite the challenges, the students evaluated their internship experience as an opportunity to acquire distinctive skills.Conclusions: Students who embarked on their internships without prior experience expressed additional and diverse aspects that warrant further investigation. Therefore, it was deemed necessary to conduct further qualitative research to broaden the perception of SARS-CoV-2 infection risk in this group of students. Keywords: Healthcare student, SARS-CoV-2 risk, perception, COVID-19 risk.